Mg and Fe Modified Ni/GDC Cermets as Sulfur Tolerant Anodes of Solid Oxide Fuel Cells - Zhang, L.; Jiang, San Ping (The Electrochemical Society, Inc., 2011)
Sulfur-tolerance of the Mg and Fe modified/doped Ni/Gd2O3-CeO2 9Ni/GDC) anodes is studied at 800˚C in H2S-H2. The polarization and impedance behavior of Ni/GDC cermet anodes indicate that Mg and Fe doping in the Ni phase of the cermet significantly improves the sulfur tolerance and performance stability of Ni/GDC anodes. SEM examination indicates that the microstructure change of the Ni phase of the Mg and particular Fe modified Ni/GDC is significantly smaller in comparison to that of pure Ni/GDC cermet anodes. The enhancement in the sulfur tolerance of Ni95Mg5/GDC and Ni95Fe5/GDC anodes is most likely due to the suppressed microstructure change of the Ni phases due to the presence of Mg and Fe dopants in the Ni/GDC cermets.